The Development of Learning Mobile Application of Latin-to-Balinese Script Transliteration - Gede Indrawan; I Ketut Pramarta (BBPSDMP KOMINFO MAKASSAR, 2019)
Balinese script writing allegedly towards extinction. The general objective of this research is to preserve this Balinese culture aspect through a technology approach. The specific objective is to develop learning mobile application of Latin-To-Balinese script transliteration, as one of the innovative technology products of the Universitas Pendidikan Ganesha – Bali, and to analyze crowd feedback of that application to know the user acceptance and to obtain feedback for future improvement. This android-based application can be used as a learning media at mandatory local content subject Balinese Language in elementary and secondary schools in Province Bali since so far, it could handle the transliteration complex behaviors based on document